Sales with Privately Made Deed Over The Object Under Hak Tanggungan Based on The Authorization to Sell in Banking Practice - Sri Budi Purwaningsih (Rechtsidee, 2014)
The extension of credit contain a risk that must be covered by the bank, because the credit is given now and pay later. To minimize the risk of loans, the bank will ask the debtor to provide collateral as a source of repayment of the debt if the debtor default or breach of the contract. According to Article 1131 Civil Code (KUH Perdata), all assets of a debtor, either moving or fixed objects, both existing and new will exist in the future, a guarantee for all debts of the engagement. This means that by itself or in order to pass laws providing collateral by a debtor to any creditor for all debtor's property. Sales with Privately Made Deed over the object in the hak tanggungan banking practices may be more effective and efficient both in terms of time and costs for the settlement of non-performing loans. But in practice, occurs some offense prescribed procedure leading to doubts about the legality aspect of sales with privately made deed over the object under hak tanggungan based on the authorization to sell in banking practice. How To Cite: Purwaningsih, S. (2014). Sales with Privately Made Deed Over The Object Under Hak Tanggungan Based on The Authorization to Sell in Banking Practice. Rechtsidee, 1(2), 191-204. doi:http://dx.doi.org/10.21070/jihr.v1i2.100